Preparation and Characterization of Zirconia Nanomaterial as a Molybdenum-99 Adsorbent - M Marlina; E. Sarmini; H Herlina; S Sriyono; I. Saptiama; H. Setiawan; K Kadarisman (PPIKSN-BATAN, 2017)
The present study deals with the synthesis and characterization of ZrO2 nanomaterial which can be used as an adsorbent for Molybdenum-99 (99Mo). The adsorbent can potentially be utilized as the material for 99Mo/99mTc generator column. Using the sol-gel method, monoclinic nanocrystalline zirconia was synthesized from zirconium oxychloride in isopropyl alcohol reacted with ammonium hydroxide solution in isopropyl alcohol resulting in a white gel. The gel was subsequently refluxed for 12 hours at 95°C and pH at 4 and then dried at 100°C. The drying gel was then calcined at 600°C for two hours. Meanwhile the orthorhombic nanocrystalline zirconia was obtained by reacting zirconium oxychloride solution with 2.5 M ammonium hydroxide solution which resulted in a white gel. The gel was then refluxed for 24 hours at 95°C and pH at 11 and then dried at 100°C. The drying gel was then calcined at 600°C for two hours. These materials were characterized using FT-IR spectroscopy, X-ray diffraction (XRD), and Transmission Electron Microscope (TEM). The Scherrer method is used for determination of crystallite size. The FT-IR spectra for both materials show absorption peak at 450-500 cm-1 which are attributed to Zr-O bond. The XRD pattern of monoclinic nanocrystalline form shows crystalline peaks at 2θ regions of 28.37°, 31.65°, 34°, 36°, and 50.3° with average crystallite size of 2.68 nm. Meanwhile, the XRD pattern of orthorhombic nanocrystalline form shows crystalline peaks at 2θ regions of 30°, 35°, 50°, and 60° with average crystallite size of 0.98 nm. The TEM micrograph indicates that the zirconia nanomaterials prepared were quite uniform in size and shape.Received: 12 November 2015; Revised: 9 September 2016; Accepted: 20 September 2016